Firn temperatures (2013-2017) and water-level changes (2015-2017) collected at three locations in a firn-aquifer region of the southeastern part of the Greenland Ice Sheet - Clément Miège; Richard Forster; Ludovic Brucker; Lora Koenig; Olivia Miller; Kip Solomon; Nick Schmerr (Arctic Data Center, 2020)
The firn temperatures were collected at three different locations (FA-13, FA-15-1 and FA-15-2) in the percolation zone of the Southeast part of the Greenland Ice Sheet, about 50 kilometers West of Helheim Glacier front. At the two FA-15 sites, water levels from pressure transducers complement the firn temperatures records. Each string of temperature sensors was installed in a borehole drilled through the aquifer, hanging in the air when above the water table and in the water when below the water table. For the two FA-15 sites, a pressure transducer was installed in the same hole, located about 1 meter below the water table and vented at the surface. Each borehole was then backfilled with unconsolidated surface snow. For FA-13 (66.1812° North, 39.0435° West, 1563 meters), firn temperatures were collected between April 09, 2013 and September 13, 2015. For FA-15-1 (66.3622° North, 39.3119° West, 1664 meters), firn temperatures and water levels were collected between April 17, 2015 and February 22, 2017. For FA-15-2 (66.3548° North, 39.1788° West, 1543 meters), firn temperatures and water levels were collected between August 9, 2015 and February 2, 2017.